2019
DOI: 10.14302/issn.2470-0436.jos-19-2602
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility and Barriers to Uptake of Ophthalmic Services among Rural Communities in the Upper Denkyira West District, Ghana

Abstract: Vision impairment and blindness remain a challenge in developing countries, especially in rural communities. Notwithstanding, VISION 2020 global initiative seeks to eliminate avoidable blindness by 2020. This community-based cross-sectional study aimed at determining the accessibility of ophthalmic services and barriers to its utilization in rural communities in the Upper Denkyira West District, Ghana. One-hundred and seventy participants from 5 randomly chosen rural communities in the district were included. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Studies in the developing countries found that lack of the awareness, availability, accessibility, and affordability of services constitute significant treatment-seeking barriers for eye health care. 7 These observations also seem to apply for Bangladesh, where 37.5% of patients attended a public health facility for eye/ear/nose/throat diseases. In comparison, 25% of them sought no treatment or sought treatment from traditional healers.…”
Section: Discussionmentioning
confidence: 93%
“…Studies in the developing countries found that lack of the awareness, availability, accessibility, and affordability of services constitute significant treatment-seeking barriers for eye health care. 7 These observations also seem to apply for Bangladesh, where 37.5% of patients attended a public health facility for eye/ear/nose/throat diseases. In comparison, 25% of them sought no treatment or sought treatment from traditional healers.…”
Section: Discussionmentioning
confidence: 93%